2022
DOI: 10.1155/2022/4031403
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0004543 Aggravates Cervical Cancer Development by Sponging MicroRNA hsa-miR-217 to Upregulate Hypoxia-Inducible Factor

Abstract: Cervical cancer (CC) is the 4th principal source of cancer death in females with 604,000 new patients and 342,000 deaths in 2020 worldwide. It has been extensively shown that circRNAs are involved in regulating CC development. Nevertheless, the function and mechanisms of hsa_circ_0004543 in regulating CC need to be clearly elucidated. Herein, hsa_circ_0004543 expressions were compared between 40 paired paracancerous and cancerous specimens from CC patients and between 6 CC cell lines and a normal human cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…51 However, Jun Liu et al confirmed the high expression of circ 0004543 in cervical cancer tissues and cell lines and its upstream regulation mechanism of HIF1α, i.e., circ 0004543 binds to hsa-miR-217 to increase the expression of HIF-1a, triggering tumorgenesis, providing us with a novel possible therapeutic target. 52 Xiwu Ouyang et al focused on the phenomenon of androgen receptor (AR) restraining HCC progression in hypoxia and demonstrated that AR/circ-LNPEP/miR-532-3p/RAB9A axis are involved; the following rescue assay also demonstrated the function and the core role in the regulation. 53 Metabolic reprogramming is a hallmark of malignancy with the deepening understanding of tumor biology and the complexity of tumor metabolism.…”
Section: Circrnas and Hypoxiamentioning
confidence: 99%
“…51 However, Jun Liu et al confirmed the high expression of circ 0004543 in cervical cancer tissues and cell lines and its upstream regulation mechanism of HIF1α, i.e., circ 0004543 binds to hsa-miR-217 to increase the expression of HIF-1a, triggering tumorgenesis, providing us with a novel possible therapeutic target. 52 Xiwu Ouyang et al focused on the phenomenon of androgen receptor (AR) restraining HCC progression in hypoxia and demonstrated that AR/circ-LNPEP/miR-532-3p/RAB9A axis are involved; the following rescue assay also demonstrated the function and the core role in the regulation. 53 Metabolic reprogramming is a hallmark of malignancy with the deepening understanding of tumor biology and the complexity of tumor metabolism.…”
Section: Circrnas and Hypoxiamentioning
confidence: 99%
“…In recent decades, the global incidence of cholangiocarcinoma has increased, particularly in Asian nations ( 6 ). Presently, the predominant approach for the treatment of most patients with cholangiocarcinoma is surgical resection in conjunction with chemotherapy or chemoradiation ( 7 ). Nevertheless, post-surgery, chemotherapy, and chemoradiation frequently give rise to a range of complications and adverse reactions, thereby contributing to an unfavorable prognosis for patients.…”
Section: Introductionmentioning
confidence: 99%